Want a worry-free trip? Seeking the optimal travel paradigm in view of public-to-individual risk perception - Chunbing Bao; Yuqiao Hui; Zhen Zhang; Qinyue Zheng; Qingchun Meng (Humanities & Social Sciences Communications)
Abstract In travel decision-making, searching for the optimal travel paradigm is crucial, with risk perception playing a pivotal role. Despite its significance, a comprehensive understanding of risk perception from various sources within the travel population and its implications for choosing the best travel mode remains limited in existing literature. This paper offers a twofold contribution to the field to address this gap. Firstly, it presents an innovative framework for identifying and quantifying risk perceptions based on travel notes employing text mining. This framework effectively captures measures of risk perception at both the public and individual levels for specific destinations. Secondly, it statistically explores the relationship between travel paradigms and the proposed risk perceptions. Using Xinjiang province as a case study, empirical analysis reveals several key findings: (1) Individual travel profiles are associated with various factors that significantly influence risk perceptions, with factors such as travel expenditure and duration exerting the greatest impact, this coincides with the common perception; (2) Other factors, including traveling in non-autumn seasons, traveling with friends, going by cruising, cycling, self-driving, staying at three-star hotels on the northern and central area of Xinjiang, and following linear and circular routes, substantially reduce tourism risk perception; and (3) Discernible differences in travel plans between males and females emerge when their risk perceptions are low. Incorporating risk perception into travel planning provides valuable insights for destination tourism risk management and local economic promotion and holds significant implications for enabling tourists to form rational risk assessments and adopt comfortable travel styles.